Is AI good for agency: Editorial - Stenalt , Maria Hvid; Hachmann, Roland (Tidsskriftet Læring og Medier (LOM), 2024)
This special issue addresses pressing questions related to the interaction between education technology and agency and motivation: how are teacher and student agency and motivation affected by education technology, and how do technology and institutional decision-making and implementation take student and teacher agency and motivation into account?